Karyotypes of some species of Cestrum, Sessea, and Vestia (tribe Cestreae, Solanaceae) - Las Peñas, Maria Laura (2006)
The somatic chromosomes of Cestrum bigibbosum Pittier, C. buxifolium Kunth, Sessea corymbosa Goudot ex Taylor and Phillips and Vestia foetida (Ruiz et Pav.) Hoffmanns, were examined by classical staining. The number 2n = 2x = 16 was found for all species. The total genome length ranged from 57.70 to 92.09 μm and the average chromosome length from 7.21 to 11.51 μm. Karyotypes were notably symmetrical. Haploid karyotype formulae were 8 m pairs (C. bigibbosum, V. foetida) or 7 m + 1 sm pairs (S. corymbiflora, C. buxifolium). Except Sessea corymbiflora in which satellites were not visualized, the remaining species showed one satellited pair. The species can be distinguished by a combination of karyotype formula, karyotype length, and the position of satellites in a particular chromosome pair. Karyotype diversification in tribe Cestreae is suggested to have been accompanied by a tendency towards slight asymmetry and increased genome length.